Morphometric discrimination of pelagic fish stocks challenged by variation in body condition. (13th September 2017) - Geladakis, George; Nikolioudakis, Nikolaos; Koumoundouros, George; Somarakis, Stylianos
Abstract: Morphometric characters have traditionally been used to describe the population structure of fishes. Body shape variation, which is often environmentally induced, may provide a good record of short-term population structuring. However, factors unrelated to environmental or genetic influences on body morphology may complicate sampling and the use of morphometric features for stock discrimination. In the present study, we used geometric morphometric variables to compare the European sardine Sardina pilchardus putative stocks of the Aegean and Ionian Seas (eastern Mediterranean). Landmark data of fish collected at seven different sites were subjected to canonical analysis of principal coordinates (CAP). The average body condition of sardines from these sites was strongly and linearly related to corresponding scores along CAP1, the axis exhibiting the highest correlation with the morphometric data cloud. The average scores along CAP2 and CAP3 appeared to be linked to morphological differentiation related to temperature effects and prey availability (mesozooplankton biomass). Despite the primary and confounding effect of body condition, discrimination of different morphotypes corresponding to the Aegean and the Ionian Sea stocks was highly significant with 81% correct reallocations for the respective CAP model.